Economic analysis of alternate Rift Valley fever control options from a multisectoral perspective - Kimani, T.M.; Schelling, E.; Ngigi, M.; Randolph, Thomas F. (International Livestock Research Institute, 2012)
Rift Valley fever is a viral zoonosis that primarily affects people, cattle, sheep, goats, camels, buffalos, dromedaries, antelopes and wildebeest. The two most recent RVF epidemics in Kenya occurred in 1997/1998 and in 2006/2007 with severe socio-economic consequences in multiple sectors of the national economy. This study was undertaken to provide policy evidence on cost-effectiveness and benefits associated with alternate control options as well as the one health institutional arrangements for its improved prevention and control from both a public health and livestock perspectives. The approach employed multistage process that involved; mapping of one health stakeholders; an institutional analysis; simulation of different options (combinations of vaccination, sanitary measures, surveillance, vector control and awareness campaigns) using an individual-based epidemiological model and economic modeling to estimate costs of control per disability adjusted live year averted and benefits to the livestock sector and national economy. Up to 28 different agencies are relevant and need to be considered in one health collaborations to RVF prevention and control. The stakeholders go beyond the line animal and public health sectors. Socio network analysis reveals denser networks and stronger relational linkages between the public health stakeholders while the reverse is true for animal health stakeholders. Centrality statistics measures of Degree, Betweeness and Closeness identified the two health sectors, and the community as being the actors who linked clusters within the network. A non health ministry emerged as the actor demonstrating the highest closeness. The study concludes that a narrow scope of one health approach through collaboration of animal and human health agencies leaving out other non health actors and the livestock keepers could weaken control of zoonoses. Preliminary cost-benefit analysis of animal vaccination demonstrates good returns to investment (cost benefit ratio of greater than 1).